TBR2 coordinates neurogenesis expansion and precise microcircuit organization via Protocadherin 19 in the mammalian cortex - Xiaohui Lv (Nature Portfolio, 2019)
The T-box protein TBR2 is involved in cortical neurogenesis expansion during neurodevelopment and is preferentially enriched in intermediate progenitors. The authors show that TBR2 coordinates neurogenesis expansion and precise microcircuit assembly in the mouse cortex via PCDH19.